TEKNIK PELAKSANAAN TERAPI PERILAKU (BEHAVIOUR) - Asrul Haq Alang (240-540X)
Behavior therapy seeks to get rid of behavioral symptoms (deviant behavior), rather than helping the individual to gain an understanding of the problems related to the client. Behavioral therapy uses learning principles to reduce or eliminate maladaptive behavior. Behavioral therapies are based on social cognitive and behavioral theories that explain learning behavior and personality. Behavioral therapists do not look for unconscious conflicts as do psychodynamic therapists or encourage individuals to develop accurate perceptions about their feelings and self, as do humanistic therapists. Behavioral therapy has few concepts. It is an inductive approach that is based on experiments and applies experimental methods to the therapeutic process.